Social Factors Contributing to the Development of Allostatic Load in Older Adults: A Correlational- Predictive Study - Alejandro Morales Jinez; Esther Gallegos Cabriales; Karen D'Alonzo; Alicia Ugarte Esquivel; Francisco Javier López Rincón; Bertha Cecilia Salazar González (Universidad de La Sabana, 2018)
Factores sociales que contribuyen al desarrollo de la carga alostática en adultos mayores: un estudio correlacional-predictivo Fatores sociais que contribuem para o desenvolvimento da carga alostática em idosos: um estudo preditivo correlacional Objective: To determine if social factors, such as housing conditions, satisfaction with one's house, neighborhood characteristics, social support, family relations and church attendance affect allostatic load in older adults. Materials and method: A correlationalpredictive, cross-sectional study was conducted. The instruments used were sociodemographic data, the perceived family relationships instrument, the Medical Outcomes Study-Social Support Survey and the abbreviated version of the Neighborhood Environment Walkability Scale. The allostatic load biomarkers used were: systolic and diastolic blood pressure, body mass index, waist circumference, waist-hip ratio, total cholesterol, high density lipoprotein, glycated hemoglobin, fibrinogen, and C-reactive protein. Sample size was estimated to contrast the no relation (R2 = 0) hypotheis in a multiple lineal regression model with 11 covariables, with a significance level of .05, power of 90% (.90), when coefficient of determination (R2) is .15, resulting in a sample of 131 older adults. The statistical analysis included descriptive measures and generalized linear models. Results: The participants had either medium- or high-risk allostatic load. Multivariate linear regression model analysis showed that better housing conditions, satisfaction with own house, presence of dead-end streets, and church attendance reduce allostatic load, while dangerous traffic increases allostatic load. Conclusions: There are several social factors contributing to the development of allostatic load in older adults. It is necessary to create nursing care strategies toward the social environment to decrease allostatic load in older adults.